2008
DOI: 10.1136/jme.2008.024307
|View full text |Cite
|
Sign up to set email alerts
|

A report on small team clinical ethics consultation programmes in Japan: Table 1

Abstract: Clinical ethics support, including ethics consultation, has become established in the field of medical practice throughout the world. This practice has been regarded as useful, most notably in the UK and the USA, in solving ethical problems encountered by both medical practitioners and those who receive medical treatment. In Japan, however, few services are available to respond to everyday clinical ethical issues, although a variety of difficult ethical problems arise daily in the medical field: termination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In a research published in 2008 within the scope of a project, 17 educators working in biomedical ethics field have conducted a clinical ethics and support activity. The results obtained from the review of the one-year activity of consultancy service carried out by this small group which was considered as the first application in this field were found positive (7). In Norway example on the other hand, Ethics Center started a project in 1993 with the support of Ministry of Health.…”
Section: Developments Of Hecs From Different Countriesmentioning
confidence: 99%
“…In a research published in 2008 within the scope of a project, 17 educators working in biomedical ethics field have conducted a clinical ethics and support activity. The results obtained from the review of the one-year activity of consultancy service carried out by this small group which was considered as the first application in this field were found positive (7). In Norway example on the other hand, Ethics Center started a project in 1993 with the support of Ministry of Health.…”
Section: Developments Of Hecs From Different Countriesmentioning
confidence: 99%
“…2 In particular, the limited availability of ethics consultation services, which has been reported by authors from different countries, fails to meet the frequent and strong requests by health workers to support their ethical difficulties in situations involving the terminally ill, patient autonomy and end-of-life decisions. 7 The delay of institutions in providing ethics consultation services is only one aspect of the inadequacy of the response to the increasing ethical difficulties in care activities. While ethical issues are present in many health school programmes, several studies highlight how basic and lifetime learning in ethics are poorly diffused among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Fukuyama et al reported the first small team HCEC services started in October 2006 in Japan, which was also the first formal HCEC published in an academic international journal from East Asia [19]. Until now, there is no formal report published in academic international journals regarding HCEC services in the health care institutions in Taiwan.…”
Section: Introductionmentioning
confidence: 99%